Drought conditions could exacerbate nitrogen and phosphorus imbalances in important European forest tree species - Wohlgemuth, Lena; Jonard, Mathieu; Schmitz, Andreas; Schmidt-Walter, Paul; Deroo, Heleen; Waldner, Peter; Cools, Nathalie; De Vos, Bruno; Verstraeten, Arne; Krüger, Inken; Thimonier, Anne; Timmermann, Volkmar; et al. (BioMed Central, 2026)
Key message: A large European forest monitoring dataset reveals a pattern of reduced foliar nitrogen (N) and phosphorus (P) concentrations following drought conditions in spruce and pine, and, in the case of P, beech and oak, often exhibiting N:P imbalances. Gradual nutritional imbalance and nutrient deficiency during droughts raise concern for tree vitality and forest carbon sequestration under climate change. Context: Nitrogen (N) and phosphorus (P) are essential nutrients for tree metabolism, forest growth, and carbon sequestration, yet the drivers of their availability to trees are often complex to untangle. Aims and methods: In this study, we investigated environmental controls of foliar N, P, and N:P based on > 4100 N and P measurements in foliage samples of main tree species (beech, oak, spruce, and pine) across 279 European monitoring sites by applying mixed regression models. Results: We found overall nutritional declines over the past three decades that ranged from − 1.8% to − 2.7% and from − 3.5% to − 4.2% per 10 years for foliar N and P concentrations respectively. At around two-thirds of monitoring sites, where foliar N:P significantly increased over the examined time span, these increases were dominated by declines in foliar P. Foliar sampling years with summer droughts (standardized precipitation evapotranspiration index < − 1.2) were associated with lower standardized foliar P concentrations in all tree species compared to average years. Conclusion: We concluded that variations in drought conditions drive foliar N and P on a short-term, mostly annual basis, while throughfall deposition of N impacted foliar N over larger time spans of several decades depending on tree species.
Keywords: forest nutrition; drought; foliage; deposition; phosphorus; nitrogen